ENHANCHING THE SECONDARY STUDENTS’ WRITING SKILLS THROUGH PROJECT BASED LEARNING - Albert Effendi Pohan (Universitas Riau Kepulauan, 2020)
This study was aimed at identifying the role of Project Based Learning implementation that were there any significant or no toward the secondary students’ writing skills at tenth grade of SMA Negeri 21 Batam. The design of this research was running by experimental research which consist of control class and experiment class. To meet the purposes of the research, 50 students from Tenth Grade of first Science class and second Science class were selected to be the participants of this research. Both of the classes first science class and second science class were given different treatment. The first science class was taught by Project Based Learning and the second science class was taught by conventional method. The data were collected through running written test which consist of pre-test and post-test (in which the participants wrote the simple descriptive text). The analysis of the data obtained from the scoring of students’ written test. The data analysis indicated that the Project Based Learning was given significant effect on enhancing the students’ writing skills. It was also found that students’ score in experimental class achieved affected result with the highest score was 92, meanwhile the lowest score was 67. The t-count was higher than t-table (Sig). (4.188 ˃ 2.011). Therefore H0 is rejected and Ha is accepted, there was significance effect of Project Based Learning toward the secondary students’ writing skill. As the implications of the study, it seems that Project Based Learning can bring helpful insight for both of secondary students and teachers on enhancing the writing skills.